Stratospheric ClOOCl chemistry at high solar zenith angles - Suminska-Ebersoldt, Olga (Forschungszentrum Jülich GmbH Zentralbibliothek, Verlag, 2012)
The photolysis rate constant of dichlorine peroxide (ClOOCl, ClO dimer), J$_{ClOOCl}$, is a critical parameter in catalytic cycles destroying ozone (O$_{3}$) in the polar stratosphere. In the atmospherically relevant wavelength region (310 – 500 nm), significant discrepancies between laboratory measurements of ClOOCl absorption cross sections and spectra cause a large uncertainty in J$_{ClOOCl}$. Previous investigations of the consistency of published J$_{ClOOCl}$ with atmospheric observations of chlorine monoxide (ClO) and ClOOCl have focused on the photochemical equilibrium between ClOOCl formation and photolysis, and thus could only constrain the ratio of J$_{ClOOCl}$ and the ClOOCl formation rate constant k$_{rec}$. Here, the atmospherically effective J$_{ClOOCl}$ was constrained independent of krec, using ClO measured in the same air masses before and directly after sunrise during an aircraft flight that was carried out as a part of the RECONCILE field campaign in winter 2010 over Kiruna, Sweden. Over sunrise, when the ClO/ClOOCl system comes out of thermal equilibrium, the influence of the ClO recombination reaction is negligible and the ClO concentration increase results from the photolysis of ClOOCl. J$_{ClOOCl}$ values based on four absorption cross sections and spectra were estimated for the atmospheric conditions on the flight track and resulting ClO concentration increases were compared with the observed ClO rise. The analysis shows, that the increase in measured ClO concentrations was significantly faster than expected from J$_{ClOOCl}$ based on the absorption spectrum proposed by Pope et al. (2007), but did not warrant cross sections larger than recently published values by Papanastasiou et al. (2009). In particular, the existence of a significant ClOOCl absorption band longwards of 420nm is not supported by the observations. The observed night-time ClO is not consistent with a ClO/ClOOCl thermal equilibrium constant significantly higher [.]